Harmonic Multivalent Functions Associated with Generalized Hypergeometric Functions - Yasin Tahs, Abdul kader; Juma, Abdul Rahman S. (Iraqi Journal of Science, 2022)
In this paper , certain subclass of harmonic multivalent function defined in the exterior of the unit disk by used generalize hypergeometric functions is introduced . In This study an attempting have been made to investigate several geometric properties such as coefficient property , growth bounds , extreme points , convolution property , and  convex linear combination .